The role of timing in assessing oral reading fluency and comprehension in Kenya. (January 2016) - Piper, Benjamin; Zuilkowski, Stephanie Simmons
Despite rapid growth in literacy-related programmes and evaluation in sub-Saharan Africa, little critical attention has been paid to the relevance of assumptions that underlie existing assessment methods. This study focuses on the issue of timing in the assessment of oral reading fluency, a critical component of successful reading (Chard, Vaughn, & Tyler, 2002; National Institute of Child Health and Human Development (NICHD), 2000; Pikulski & Chard, 2005). Within the context of the Primary Math and Reading Initiative, a randomized controlled trial of several instructional interventions in Kenya, timed and untimed Early Grade Reading Assessment (EGRA) oral reading fluency and reading comprehension tasks were administered to 4385 students in 95 government and 125 informal schools. Using the data from the EGRA – whose administration has expanded within sub-Saharan Africa recently – we found that students did not perform significantly better on the assessments when they had more time. This pattern largely held when we examined the effects disaggregated over student ability level. This suggests that timed assessments, which are faster to administer and logistically easier, are appropriate for use in Kenya.